INFLASI TERHADAP LABA PERUSAHAAN PERBANKAN DI INDONESIA - Laynita Sari; Renil Septiano (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to examine whether there is an effect of inflation on the profits of Indonesian banking companies in 2020-2022. The population in this study is all banking companies listed on the Indonesia Stock Exchange in 2020-2022. The number of samples in this study was 34 banking companies that met the criteria. The sampling technique uses purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis with E-Views version 12. The results of this study provide empirical evidence that partially the inflation variable has a positive effect on company profits